Entrapment of a neutral Tm(III)‐based complex with two inner‐sphere coordinated water molecules into PEG‐stabilized vesicles: towards an alternative strategy to develop high‐performance LipoCEST contrast agents for MR imaging. (23rd April 2014) - Chahid, Bochra; Vander Elst, Luce; Flament, Julien; Boumezbeur, Fawzi; Medina, Christelle; Port, Marc; Muller, Robert N.; Lesieur, Sylviane
<x xml:space="preserve">Abstract</x> Chemical exchange saturation transfer (CEST) probes issued from the encapsulation of a water proton paramagnetic shift reagent into the inner aqueous volume of lipid vesicles provide an emerging class of frequency‐selective contrast agents with huge potential in the field of molecular magnetic resonance imaging (MRI). This work deals with the generation of such LipoCEST agents properly designed to optimize, under isotonic conditions, the chemical shift offset of the intra‐liposomal water protons as well as the number of exchangeable protons under reasonably low radiofrequency (RF) fields of saturation. The strategy lies in the loading of poly(ethylene glycol)‐stabilized nanosized liposomes with uncharged lanthanide chelates, binding more than one water molecule in the first hydration sphere, exemplified here by [Tm(III)–DO3A (H2O)2] complex. The key properties of the probes are demonstrated by complementary NMR investigations. The residence lifetime of the water molecules coordinated to the lanthanide center was outstandingly short (9.5 ± 0.2 ns from 17O NMR), and indeed relevant for effective LipoCEST responsiveness. The 1H NMR CEST spectra (7.01 T magnetic field) prove that the theoretically expected optimal sensitivity can be approximated in the nanomolar concentration range, at reasonably low RF presaturation pulses (6.7–12 μT) and saturation frequency offsets of the intra‐liposomal water protons beyond 10 ppm, making possible selective irradiation in biological environment. CEST‐MRI images (7.01 T magnetic field and 10–12 μT RF pulse) explicitly confirm the interest of these newly conceived LipoCEST agents, indeed among the most efficient ones developed so far under isosmotic conditions. Copyright © 2014 John Wiley & Sons, Ltd.